2021
DOI: 10.1002/uog.22009
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome at 2 years of corrected age in fetuses with increased nuchal translucency thickness and normal karyotype compared with matched controls

Abstract: What are the novel findings of this work?This is the first study to use an objective psychomotor test to compare the developmental quotient (DQ) of infants who had increased fetal nuchal translucency (NT) thickness in the first trimester and normal karyotype with that of a matched control group with normal NT. The mean DQ in the increased-NT group was significantly lower than that in the control group at 2 years of corrected age; however, it was within the normal range expected for that age, even when NT was >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Using objective psychomotor testing at 2 years corrected age, the investigators found that the mean developmental quotient of the increased NT group was within the normal range, although it was lower than the control group. These reassuring findings also applied for those who had an isolated NT ≥3.5 mm 60 …”
Section: Final Assessmentmentioning
confidence: 89%
See 2 more Smart Citations
“…Using objective psychomotor testing at 2 years corrected age, the investigators found that the mean developmental quotient of the increased NT group was within the normal range, although it was lower than the control group. These reassuring findings also applied for those who had an isolated NT ≥3.5 mm 60 …”
Section: Final Assessmentmentioning
confidence: 89%
“…Women and their partners may wish to discuss TOP early in the journey, particularly if the NT is large ( 42 control group with normal NT measurements. 60 Using objective psychomotor testing at 2 years corrected age, the investigators found that the mean developmental quotient of the increased NT group was within the normal range, although it was lower than the control group. These reassuring findings also applied for those who had an isolated NT ≥3.5 mm.…”
Section: What Should I Tell My Family and Friends? Can I Have A Termi...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, the algorithms could accurately classify fetal brain segments in fetuses with a normal and an increased NT. Our findings may lay the foundation for further research and early diagnosis of fetal brain abnormalities, specifically in fetuses with an increased NT that comprise a high‐risk population for neurodevelopmental sequela 24–26 …”
Section: Discussionmentioning
confidence: 83%
“…Our findings may lay the foundation for further research and early diagnosis of fetal brain abnormalities, specifically in fetuses with an increased NT that comprise a high-risk population for neurodevelopmental sequela. [24][25][26] Based on the two methods we tested, the processed images provided a convenient and accurate platform for recognizing the fetal brain cortex, a structure with a width of 2-3 mm at 12-14 week gestation. The more stable segmentation results produced by the TWS method compared to the SRM method (a similar MAPE with a lower standard deviation) may be attributed to the ability of the TWS to adjust itself for specific data, in contrast to the SRM, that is not trainable and based on a predefined-fixed threshold.…”
Section: Discussionmentioning
confidence: 99%